Cellular lipid production by the fatty acid synthase-duplicated Lipomyces kononenkoae BF1S57 strain for biodiesel making. (May 2020) - Chen, Lu; Zhang, Yu; Liu, Guang-Lei; Chi, Zhe; Hu, Zhong; Chi, Zhen-Ming
Abstract: Lipomyces starkeyi has been regarded as one of the model oleaginous yeasts. However, in this study, Lipomyces kononenkoae BF1S57 strain was found to be able to yield 60.06% (w/v) lipids (11.3 g/L lipids) from 90.0 g/L glucose, its cell mass was 18.8 ± 0.3 g/L within 96 h of a 10-L fermentation. Furthermore, the genome of L. kononenkoae has two copies of the genes encoding the β-subunit and α-subunit of fatty acid synthase, respectively. This may be related to high lipid contents in its cells. Over 94% of the fatty acids of the extracted lipids produced by L. kononenkoae BF1S57 strain was C16:0, C16:1, C18:0, C18:1 and C18:2 fatty acids. The properties of the prepared biodiesels in this study totally met the requirements of US biodiesel ASTM D6751 and EU biodiesel EN 14214. All these results demonstrated that the produced cellular lipids could be used as raw materials for biofuel production. Highlights: L. kononenkoae BF1S57 strain yielded 60.06% (w/v) lipids within 96 h of the 10-L fermentation. Over 94% of the fatty acids of the extracted lipids was C16:0, C16:1, C18:0, C18:1 and C18:2 fatty acids. The prepared fatty acid methyl esters could be used as biodiesels.